2012
DOI: 10.1016/j.jcrs.2012.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Response of the posterior corneal surface to myopic laser in situ keratomileusis with different ablation depths

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…In our series, loss of lines of CDVA was only detected in 1 eye (0.99%), as in our previous series, 2 whereas Tsiklis et al 5 did not report any visual loss after LASIK with the Pulzar laser system in a smaller sample. 31 No significant changes were observed in the magnitude of ORA, which was consistent with the lack of significant changes in PCA and in astigmatism of the crystalline lens, a structure that is not affected by the surgical procedure. All these refractive and visual outcomes were also equivalent or even better than those reported with the last generation of excimer lasers.…”
Section: Discussionsupporting
confidence: 63%
“…In our series, loss of lines of CDVA was only detected in 1 eye (0.99%), as in our previous series, 2 whereas Tsiklis et al 5 did not report any visual loss after LASIK with the Pulzar laser system in a smaller sample. 31 No significant changes were observed in the magnitude of ORA, which was consistent with the lack of significant changes in PCA and in astigmatism of the crystalline lens, a structure that is not affected by the surgical procedure. All these refractive and visual outcomes were also equivalent or even better than those reported with the last generation of excimer lasers.…”
Section: Discussionsupporting
confidence: 63%
“…This study did not fi nd a statistically signifi cant difference in MPE measured before and after LASIK using the DRS system. Smadja et al 20 found mild posterior steepening early after myopic LASIK, with a shift to the preoperative level between 1 and 3 months using the Galilei. This fi nding is consistent with our results that show minimal change in MPE at least 6 weeks after surgery.…”
Section: A B Cmentioning
confidence: 99%
“…The software has enhanced the posterior edge location and uses ray tracing with the Snell law of refraction through the anterior surface to locate and help in reliably reconstructing the posterior surface. 20 Two snapshot Placido images are acquired and used for anterior curvature, one each with the Scheimpfl ug camera system at zero degrees and rotated 90 degrees.…”
Section: Galilei Dual Rotating Scheimpflug Analyzer: Drsmentioning
confidence: 99%
“…Auf die unmittelbare Entfernung von Teilen des stromalen Kollagennetzes im Rahmen der primären Korrektur kann das Gewebe mit unerwünschten Veränderungen reagieren. So kann es nach myopen Korrekturen mit intendierter Hornhautabflachung durch die Gewebsentfernung auch zur Aufsteilung der biomechanisch weniger rigiden posterioren Hornhaut mit konsekutiver optischer Regression kommen [23].…”
Section: Remodellingunclassified